Construção Metodológica da Educação Física Escolar: uma proposta conjunta professor-aluno - Santos, Juan Parente (2010)
There is, in physical education classes at the Federal Institute of Education, Science and Technology (IFCE), Crato campus a great disinterest by the students to participate in those activities still unknown to their surroundings, making the timing of the class something uncomfortable and most often unpleasant, where the student is present for duty. Bolstered by the Law of Directives and Bases for National Curriculum, a proposal was developed which allowed the student of physical education, the freedom of choices of the content of their lessons, making the process of teaching and learning, making classes more enjoyable, participatory and breaking the traditional view of the teacher and the student pass the contents just learning, there is a division of responsibilities and autonomy of great value to everyone involved in this medium. Thus, the aim of the study is to analyze the meanings that were assigned by high school students to the physical education curriculum component from a methodological intervention joint construction of teacher - student. For both the specific objectives sought to identify and compare these two meanings in high school classes at the beginning and the end of the intervention. This is a qualitative research intervention, the line of research teaching and learning processes. The participants were a total of ten (10) students randomly selected from two classes of second year of vocational technical education that has been contemplated by the intervention. The instruments used were two identical questionnaires with questions about the physical education they had in 2008 and 2009, both applied at the end of the school year in question. For data analysis we used the method to map the association of ideas and techniques of content analysis, which led us to conclude that the change in activity indicates a greater inhibition suggesting an estrangement of students with an alternative perspective and the difficulty of processing culture of a traditional classroom.